Evaluation of miR-34b/c polymorphisms to the risk of ischemic stroke. Issue 8 (August 2020) - Wei, Guijiang; Liao, Changpin; Jian, Chongdong; Liang, Limei; Liu, Jia; Tang, Yujin; Wei, Yesheng
Abstract : Objectives: Polymorphisms in microRNA genes are related to the risk of ischemic stroke, but the association between miR-34b/c polymorphisms and the risk of ischemic stroke has not been reported. Methods: MiR-34b/c rs2187473 and rs4938723 polymorphisms were genotyped by Snapshot assay among 495 controls and 492 ischemic stroke patients. Expression levels of miR-34b and miR-34c were quantified by real-time PCR. Transcriptional activity of miR-34b/c promoter was measured by luciferase reporter assay. Results: Rs4938723 was associated with an increased risk of ischemic stroke in our study (CC versus TT: OR = 2.34, 95% CI = 1.47–3.72, P  = 0.001; C versus T: OR = 1.37, 95% CI = 1.12–1.68, P  = 0.002; CC versus TT + TC: OR = 2.12, 95% CI = 1.37–3.29, P  = 0.001). The expression levels of miR-34b and miR-34c were significantly downregulated in cases by contrast with controls ( P  < 0.05). Further analysis demonstrated that the expression levels of miR-34b and miR-34c were also downregulated in the individuals carrying rs4938723 CC genotype by contrast with that carrying TT + TC genotypes ( P  < 0.05). The result of luciferase reporter assay showed that rs4938723C allele decreased the transcriptional activity of miR-34b/c promoter compared with rs4938723 T allele. Conclusion: Our study showed a positive relation between the miR-34b/c rs4938723 polymorphism and the risk of ischemic stroke, which indicated that rs4938723 may be used for ischemic stroke prediction or therapy in the future. Abstract : Supplemental Digital Content is available in the text